The treatment of primary cutaneous lymphoma. Recommendations of the Polish Lymphoma Research Group (PLRG) - Sokołowska-Wojdyło, Małgorzata; Lech-Marańda, Ewa; Placek, Waldemar; Meder, Janusz; Maciej Zaucha, Jan; Walewski, Jan (Dermatology Review/Przegląd Dermatologiczny, 2010)
Primary cutaneous lymphoma is a heterogeneous group of lymphoid neoplasms, mostly of T-cell origin, defined by the initial and clinically dominant involvement of skin. Clinical course and prognosis of these diseases is distinct from other nodal or extranodal lymphomas. Cutaneous lymphomas usually have a very prolonged course and are incurable in most cases. The diagnosis and treatment planning are best applied if a multidisciplinary approach involving dermatologists, oncologists, haematologists and pathologists is adopted. The Cutaneous Lymphoma Section, created within the Polish Lymphoma Research Group in 2009, set out to reach a consensus on treatment guidelines that would be acknowledged by major specialties involved in the management of these patients. The guidelines are consistent with published international recommendations and supported by current practice of the Polish dermatology and haematology-oncology centres.